2014
DOI: 10.1016/j.numecd.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Salt loading has a more deleterious effect on flow-mediated dilation in salt-resistant men than women

Abstract: Background and Aims Dietary sodium loading has been shown to adversely impact endothelial function independently of blood pressure (BP). However, it is unknown whether dietary sodium loading impacts endothelial function differently in men as compared to women. The aim of this study was to test the hypothesis that endothelial-dependent dilation (EDD) would be lower in men as compared to women in response to a high sodium diet. Methods and Results Thirty subjects (14F, 31±2y; 16M, 29±2y) underwent a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…Third, while the difference in sex distribution between the African American and Caucasian cohorts was not statistically significant, we recognize it could be meaningful. However, one might speculate the proportion of females in the African American cohort would lead to less BP responsiveness, as we have previously shown females are less susceptible to endothelial dysfunction following high dietary salt ( Lennon-Edwards et al, 2014 ) and females demonstrate less salt sensitivity compared to male counterparts ( Bursztyn and Ben-Dov, 2013 ; Elijovich et al, 2016 ). Nonetheless, we observed greater BP responses for a given increase in serum sodium in the African American cohort.…”
Section: Discussionmentioning
confidence: 97%
“…Third, while the difference in sex distribution between the African American and Caucasian cohorts was not statistically significant, we recognize it could be meaningful. However, one might speculate the proportion of females in the African American cohort would lead to less BP responsiveness, as we have previously shown females are less susceptible to endothelial dysfunction following high dietary salt ( Lennon-Edwards et al, 2014 ) and females demonstrate less salt sensitivity compared to male counterparts ( Bursztyn and Ben-Dov, 2013 ; Elijovich et al, 2016 ). Nonetheless, we observed greater BP responses for a given increase in serum sodium in the African American cohort.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of two groups of men and women who followed either a low salt or high salt diet for 5 days, the NO component of the forearm blood flow response to Ach was reduced in the group of men who consumed the high salt diet compared to the group that consumed the low salt diet whereas there was no difference between the 2 groups of women (40). More recently, 7 days of high salt reduced FMD in both normotensive salt resistant men and women however FMD was lower in the men compared to women on the high salt diet (41). These two studies suggest a potentially greater sensitivity of the vasculature to high salt in men.…”
Section: Dietary Salt and Endothelial Functionmentioning
confidence: 99%
“…Potassium is notable for its BP lowering effects in those with pre-hypertension and hypertension and in the presence of an elevated sodium intake [2,5,28]. Our group has previously demonstrated that a high sodium diet has BP independent effects on endothelial function [12,13]. What remained unknown however, was whether potassium could attenuate the effects of dietary sodium in the absence of a change in BP in salt-resistant adults.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, salt-sensitive rodents supplemented with potassium while consuming a high salt chow were protected against vascular injury [10] and had improved left ventricular relaxation as assessed by echocardiography [11]. We have previously shown that chronic high dietary sodium intake has detrimental effects on the vasculature, independent of or before any changes in BP in salt-resistant adults [12,13]. To date, studies that have evaluated the role of potassium on sodium have been acute and focused on the post-prandial changes in endothelial function.…”
Section: Introductionmentioning
confidence: 99%